The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jad.2017.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Childhood social adversity and risk of depressive symptoms in adolescence in a US national sample

Abstract: Objective Childhood social adversity has been associated with an increased risk of depression and other psychiatric disorders in adolescence and early adulthood. However, the role of timing and accumulation of adversities has not yet been established in longitudinal studies. We examined the association between childhood adversities and adolescent depressive symptoms, and the impact of timing and accumulation of adversity. Method Longitudinal data were obtained from the Child Development Supplement to the Pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 48 publications
(92 reference statements)
6
23
0
Order By: Relevance
“…Like previous studies of childhood adversity in population-based samples (Björkenstam et al, 2017;Mersky et al, 2013;Perales et al, 2013;St Clair et al, 2015), although many of our study participants reported low levels of adversity throughout childhood, more than one-third experienced mild levels and about one-sixth were exposed to moderate or higher levels of adversity at some time during childhood. Like previous studies of childhood adversity in population-based samples (Björkenstam et al, 2017;Mersky et al, 2013;Perales et al, 2013;St Clair et al, 2015), although many of our study participants reported low levels of adversity throughout childhood, more than one-third experienced mild levels and about one-sixth were exposed to moderate or higher levels of adversity at some time during childhood.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Like previous studies of childhood adversity in population-based samples (Björkenstam et al, 2017;Mersky et al, 2013;Perales et al, 2013;St Clair et al, 2015), although many of our study participants reported low levels of adversity throughout childhood, more than one-third experienced mild levels and about one-sixth were exposed to moderate or higher levels of adversity at some time during childhood. Like previous studies of childhood adversity in population-based samples (Björkenstam et al, 2017;Mersky et al, 2013;Perales et al, 2013;St Clair et al, 2015), although many of our study participants reported low levels of adversity throughout childhood, more than one-third experienced mild levels and about one-sixth were exposed to moderate or higher levels of adversity at some time during childhood.…”
Section: Discussionsupporting
confidence: 59%
“…Young adults in the trajectory groups characterized by moderate levels of adversity at one or more time points (i.e., the increasing, decreasing, and stable-high groups) experienced more adverse depression outcomes than those with consistently low levels of adversity throughout childhood, reflecting the well-established association between childhood adversity and poorer mental health (Benjet et al, 2010;Björkenstam et al, 2017;Dunn et al, 2017Dunn et al, , 2018Gilman et al, 2003;Mersky et al, 2013;Oldehinkel & Ormel, 2015;Schilling et al, 2007Schilling et al, , 2008. These F I G U R E 3 Trajectories of adversity from birth through age 11.5 years (n = 9,665) findings highlight the importance of considering adverse exposures at multiple time points throughout childhood to capture the potential for health risks as a result of childhood circumstances.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among a representative sample of adolescents in Seattle, Washington, family annual income was only found to be significantly associated with adolescent depressive symptoms for those with low family income after controlling for life events within the past 6 months and no longer significant after adjusting for family environment (Tracy, Zimmerman, Galea, McCauley, & Vander Stoep, ). In a longitudinal study conducted across the United States on children 0–18 years old, family poverty at any period of development was not associated with increased odds of internalizing index scores or depression after controlling for all covariates (Björkestam, Pebley, Burström, & Kosidou, ). This is consistent with our finding that family income does not have as much bearing on depressive symptoms among adolescents as neighborhood poverty, especially if the adolescent lives in a poor neighborhood.…”
Section: Discussionmentioning
confidence: 94%